2021
DOI: 10.1039/d1qi00464f
|View full text |Cite
|
Sign up to set email alerts
|

An octahedral cobalt(iii) complex based on cheap 1,2-phenylenediamine as a bifunctional metal-templated hydrogen bond donor catalyst for fixation of CO2 with epoxides under ambient conditions

Abstract: Hydrogen bond donors (HBD) are a sustainable privileged class of catalysts which are broadly used for the activation of compounds in synthetic chemistry. Among them, the metal-templated HBD complexes present...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…Notably, no kinetic resolution was observed for monosubstituted epoxides in the case of the catalyst Δ­( S , S )- 1b I – . We assume that the HBD ability of the Co­(III) complexes is responsible for the epoxide activation via weak hydrogen-bonding interactions and that the reaction mechanism is analogous to the mechanism described in our previous reports. , …”
Section: Results and Discussionmentioning
confidence: 48%
“…Notably, no kinetic resolution was observed for monosubstituted epoxides in the case of the catalyst Δ­( S , S )- 1b I – . We assume that the HBD ability of the Co­(III) complexes is responsible for the epoxide activation via weak hydrogen-bonding interactions and that the reaction mechanism is analogous to the mechanism described in our previous reports. , …”
Section: Results and Discussionmentioning
confidence: 48%
“…Moreover, the epoxide opening products by water or ethanol were not observed. Thus, the water, ethanol and DMSO molecules are functioning as competitive H‐bond acceptor inhibitors, preventing the epoxide activation by the HBD catalyst Λ( R , R )‐ 2 [15d] …”
Section: Resultsmentioning
confidence: 99%
“…Based on the previous works, [15d,37] we have proposed a reaction mechanism consisting of four steps (Figure 3). Notably, previous investigations showed that attack of an iodide anion at both α‐ [15d,24] and β‐carbons [23] of IM1 are feasible (blue and red arrows in Figure 3), so we consider both these routes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations